Identification and characterisation of a Novel SXT/R391 ICE mobile genetic element isolated from an Irish wastewater environment. Issue 5 (27th May 2022) - Ryan, Michael P; Slattery, Shannon; Pembroke, J Tony
Abstract : Human and animal pathogenic bacteria are constantly being released into the environment through human activity. Many of these organisms can harbour genes such as virulence genes, antibiotic resistance and heavy metal resistance genes that are inserted into plasmids, transposons and Integrating Conjugating elements (ICEs), leading to potential spread. Such spread can be detected among water and soil communities and in particular in wastewater treatment plants. This makes wastewater and treatment plants a potential reservoir for mobile genetic elements including SXT/R391 ICEs, commonly detected amongst enterobacterial genera. Many plasmid and ICE genomes have been detected serendipitously from clinical sources but few have been identified without selection. Here we examined a domestic wastewater treatment plant to identify, isolate and characterize SXT/R391 ICE's without selection. Standard microbial replica plating in conjunction with ICE specific (conserved integrase gene) PCR techniques were employed to identify an SXT/R391 ICE MGE using a range of enterobactial selective media. A Novel SXT/R391 ICE MGE was identified from a wastewater Proteus mirabilisstrain. Whole genome sequencing using Ilumina sequencing technology revealed a novel 81 kb element which on annotation contained 75 open reading frames. The "hotspot regions", which contain adaptive genes, encoded a novel bacteriophage defence mechanisms but lacked other selectable determinants. With the continuous arms race between bacteria and phage, bacteria have developed novel resistance mechanism systems that protect the bacteria from phage. Such systems may be key adaptive mechanisms harboured by ICEs particularly in wastewater systems which will contain large phage populations.